Emphasizing the Active and Strategic Role of Umar bin Khattab in Shaping the Foundations of the Islamic State - Zahran, Muhammad Fajri; Maulina, Gita Dwi; Pradita, Eka Ayu (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
As the second caliph, Umar was known not only for his firm leadership but also for the innovative policies he implemented. This study aims to explore the active and strategic role of Umar bin Khattab in shaping the foundations of the Islamic state. Through an analysis of the governance system he established, the application of Islamic law, and the expansion of the caliphate's territory, this research illustrates how Umar succeeded in creating stability and order within the newly formed Islamic society.In addition, the study examines social policies that supported public welfare, infrastructure development, and the importance of consultation (shura) in decision-making. These findings are expected to provide a deeper understanding of Umar bin Khattab’s legacy and its impact on the future development of the Islamic state. With a comprehensive approach, the results of this research affirm that Umar’s contributions to education and the dissemination of knowledge were also highly significant in fostering an educated generation.